9B.03: A NOVEL INSERTIONAL SOMATIC KCNJ5 MUTATION IN AN AUSTRALIAN PATIENT WITH AN ALDOSTERONE PRODUCING ADENOMA. (June 2015) - Xu, S.; Hardege, I.; Murthy, M.; Gordon, R.; Stowasser, M.; O'Shaughnessy, K.
Abstract : Objective: Primary aldosteronism (PA), in which there is excessive and autonomous adrenal production of aldosterone, accounts for around 5–10% of hypertension. PA may be unilateral (usually aldosterone-producing adenoma [APA]) or bilateral (usually adrenal hyperplasia). Recently, somatic mutations in KCNJ5 (encoding a potassium channel) have been detected in about 40% of surgically removed APAs. The aim of this study was to screen for additional somatic mutations in KCNJ5 in a cohort of APAs removed from 87 Australian patients. Design and method: The full-length coding sequence and flanking regions of KCNJ5 in APA and adjacent cortex was resequenced. Functional changes caused by a novel mutation were studied by expressing wild-type (WT) or the mutant KCNJ5 channel in Xenopus oocytes (to examine electrophysiological effects) and transfecting empty GFP vector or the GFP-tagged mutant channel in human adrenocortical carcinoma (H295R) cells (to assess aldosterone release). Results: KCNJ5 mutations were detected in 37 APAs, and included the previously reported E145Q (n = 3), G151R (n = 20) and L168R (n = 13) mutations plus a novel 12-bp mutation, c.414–425dupCGCTTTCCTGTT (A139_F142dup) that duplicates the AFLP sequence just upstream of the selectivity filter. No mutations were found in adjacent cortices. On expression in Xenopus oocytes, the A139_F142dup mutation reduced the resting membrane potential and channel selectivity for potassium (K/Na permeability ratio 31 in WT KCNJ5 channels vs 7 in the A139_F142dup mutant). When transfected into H295R cells, A139_F142dup increased basal aldosterone release 2.3-fold over WT. This was not increased further by incubation with ATII. Clinically, the 54-year-old male from whom the mutation-bearing APA was removed had relatively severe PA with resistant hypertension, markedly elevated aldosterone/renin ratio (aldosterone 490 pmol/L, renin 2 mU/L, ratio 296) and an 11 mm left adrenal tumour on CT with lateralization to that side on adrenal venous sampling. Conclusions: Resequencing of a large Australian cohort of patients with APA further confirmed the major role of KCNJ5 somatic mutations in APA. The novel duplication mutation we report here has similar functional effects to the other mutations affecting the selectivity filter of the KCNJ5 channel with reduced membrane polarization, reduced selectivity to K and increased aldosterone release.